2011
DOI: 10.1586/ehm.11.23
|View full text |Cite
|
Sign up to set email alerts
|

Stem-cell transplantation in children and adults with sickle cell disease: an update

Abstract: Sickle cell disease (SCD) is associated with significant morbidity, a decreased lifespan and a poor quality of life. While there is increasing evidence that hydroxyurea can improve the course of severe SCD, hematopoeitic stem-cell transplantation (HSCT) remains the only curative option for SCD. Multicenter trials have shown that HSCT after myeloablative conditioning has excellent outcomes in children with SCD, with an overall survival ranging from 93 to 97% and an event-free survival between 82 and 86%. With b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…As of 2011, 1000 children are born with sickle cell disease (SCD) annually in the United States, with over 100,000 people living with the disease [1]. SCD is an hereditary hemoglobinopathy that negatively impacts quality of life and shortens life expectancy in affected individuals [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As of 2011, 1000 children are born with sickle cell disease (SCD) annually in the United States, with over 100,000 people living with the disease [1]. SCD is an hereditary hemoglobinopathy that negatively impacts quality of life and shortens life expectancy in affected individuals [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…While the numbers of children receiving transplant have continued to grow and now total in the hundreds, the majority are still performed with myeloablative conditioning (recently reviewed in [31]). The outcomes of these transplants in children are generally good with high levels of disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review demonstrated that introduction of an evidencebased guideline initiating mandatory incentive spirometry in children with SCD admitted for non-respiratory complaints resulted in a reduced number of transfusions and ACS episodes [33]. Stem cell transplantation in adults and children has been associated with no recurrence of painful crisis in those with stable engraftment [34]. The best results were obtained in young children who have HLA-identical sibling donors and transplanted early in the course of their disease [35].…”
Section: Preventionmentioning
confidence: 99%